AVALIAÇÃO DE SOBREVIVÊNCIA A CAMPO DE MUDAS FLORESTAIS NA REGIÃO DE AQUIDAUANA-MS - SILVA, Felipe Mateus Cardoso; COUTO, Allan Motta; NUNES, Irineu Barros; ALVES, Airton Elb Pereira; LIMA, Edivan Melo (ANAIS DO ENIC, 2017)
-